TURNOVER INTENTIONS OF MALAYSIAN HOTEL EMPLOYEES: THE ROLE OF HUMAN RESOURCE MANAGEMENT PRACTICES AND TRUST IN ORGANIZATION - HEMDI, MOHAMAD ABDULLAH; MOHD. NASURDIN, AIZZAT (ITB Journal Publisher, LPPM ITB, 2005)
Although numerous studies on turnover intentions have been undertaken in the past, none have systematically investigated the relationships between employees’ perceptions of HRM practices,their attitude towards the organization (trust in organization), and their behavioral intentions (turnover intentions). Thus, the objective of this study is to investigate the impact of employees’perceptions of their organization’s human resource management (HRM) practices on their turnoverintentions. The influence of trust in the organization as a mediator in the proposed relationship is also examined. Survey data were gathered from operational employees attached to large hotels in Malaysia. 380 usable questionnaires were used in the statistical analyses. The results indicated that the hypothesized linkage between HRM practices and trust in organization as well as between HRM practices and turnover intentions were partially supported. The mediating role of trust in organization was also partially supported. Implications and limitations of the findings are specified. Finally, directions for future research are suggested.